Purification and Characterization of Lectins from Abrus Species. - Caiquo, Aspect Wallace Kyemenu (Obafemi Awolowo University, 2014)
Saline extracts prepared from Abrus precatorius and Abrus fructiculosus seeds agglutinated red blood cells. The agglutination was inhibited by D-galactose and lactose. The lectins bound to Sepharose 6B and were eluted with D-galactose. These lectins were separated into an agglutinin and a toxin by chromatography on Diethyl amino ethyl (DEAE) cellulose. The toxin from Abrus fructiculosus seed was named fructin' to distinguish it from Abrus precatorius seed toxin, abrin.